Capacity Building for Nurses in Hospitals - Suprapto Suprapto (Asia Pacific Journal of Management and Education (APJME), 2022)
Nurses in carrying out their duties require an increase in ability, expertise, and skills in carrying out health care tasks to meet the level of patient satisfaction.Â  The purpose of this study is to analyze the capacity development of nurses in hospitals. The researcher uses qualitative research whose data sources used are primary and secondary data sources. The data is collected by observations, interviews, and document studies. Data analysis used is qualitative descriptive through interpretation and deep meaning by simplifying data, presenting data, making conclusions, and validating data by triangulation of data. The results showed that the process of developing nurse capacity has been carried out through changing systems of integrated nurse capacity building patterns and in-house training; determining factors determining nurse capacity development as follows; leadership; commitment; culture; spiritual; and technology. Later the researcher conclude that the strategy of increasing the capacity of nurses in health services can be realized through education and training based on spiritual and technological aspects in developing the capacity of nurses in hospitals.